Sex Difference in Meningococcal Disease Mortality, New York City, 2008–2016. (2nd March 2018) - Bloch, Danielle; Murray, Kenya; Peterson, Eric; Ngai, Stephanie; Rubinstein, Inessa; Halse, Tanya A; Ezeoke, Ifeoma; Miller, Laura; Arakaki, Lola; Ramautar, Arianne; Antwi, Mike; Del Rosso, Paula; et al.
Abstract : Compared with national rates, invasive meningococcal disease case fatality rates are higher in New York City. Increased mortality was found among females during 2008–2016 compared with males and was associated with presentation of altered mental status. Abstract: Background: The case fatality rate (CFR) from invasive meningococcal disease (IMD) in New York City (NYC) is greater than national figures, with higher rates among females than males across all age groups. Methods: We conducted a retrospective cohort study among 151 persons aged ≥15 years diagnosed with IMD in NYC during 2008–2016 identified through communicable disease surveillance. We examined demographic, clinical, and community-level associations with death to confirm the elevated risk of mortality among female IMD patients after adjusting for confounders and to determine factors associated with female IMD mortality. Relative risks of death were estimated using multivariable log-linear Poisson regression with a robust error variance. Results: Females had a higher CFR (n = 23/62; 37%) following IMD than males (n = 17/89; 19%) (adjusted relative risk [aRR], 2.1; 95% confidence interval [CI], 1.2–3.8). Controlling for demographic and clinical factors, there was a significant interaction between sex and fatal outcomes related to meningitis: the relative risk of death for females with meningitis was 13.7 (95% CI, 3.2–58.1) compared with males. In the model restricted to females, altered mental status (aRR, 7.5; 95% CI, 2.9–19.6) was significantly associated with an increased risk of death. Conclusions: Female mortality from IMD was significantly increased compared with males, controlling for other predictors of mortality. Sex-based differences in recognition and treatment need to be evaluated in cases of meningococcal disease. Our study highlights the importance of analyzing routine surveillance data to identify and address disparities in disease incidence and outcomes.